Intellectual Property in the Managerial Portfolio - OÂ'Connor, Thomas S (Business Expert Press, 2012)
Ebook from IG Library ; Intellectual Property Rights have been a part of the American pantheon of types of Property Rights since the beginning of the nation, but using the term to describe a particular type of property right is a new phenomenon dating to the second half of the last century. The recognition of the importance of protection of intellectual property rights became extremely important and distinctly more difficult at that time as new technologies made it possible for unscrupulous 'intellectual property pirates' to steal, or otherwise make off with the intellectual property of the unaware. This book introduces the reader to the underlying logic of intellectual property rights - how one can acquire them, why they exist, the benefits derived from their ownership, and how they can be protected from the unscrupulous. Legal and common-sense alternatives that provide the keys to protection are outlined and instructions on their use revealed. The availability of intellectual property rights protection, both domestic and international, is outlined and discussed, as are the history of and current trends relevant to the legal rights of the intellectual property owner and the limits of protection provided by the law and by extralegal alternatives of providing protection. The author has published extensively in the field, and has been an expert witness in a number of significant legal cases in which the interpretation and application of intellectual property concepts were tested.